2019
DOI: 10.1002/adhm.201900929
|View full text |Cite
|
Sign up to set email alerts
|

Materials Stiffness‐Dependent Redox Metabolic Reprogramming of Mesenchymal Stem Cells for Secretome‐Based Therapeutic Angiogenesis

Abstract: Cellular redox metabolism has emerged as a key tenet in stem cell biology that can profoundly influence the paracrine activity and therapeutic efficacy of mesenchymal stem cells (MSCs). Although the use of materials cues to direct the differentiation of MSCs has been widely investigated, little is known regarding the role of materials in the control of redox paracrine signaling in MSCs. Herein, using a series of mechanically tunable fibronectin‐conjugated polyacrylamide (FN‐PAAm) hydrogel substrates, it is sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…When ADSCs reached 60%-80% confluency on Cyto-MCs, differentiation process was initiated as previously described. [49][50][51] As shown in the nucleus-stained (DAPI) images of Cyto-MCs (Figure 6C), cell proliferated slower during differentiation as cell densities on Cyto-MCs cultured in DMEM were higher than in adipogenic medium (AM) and osteogenic medium (OM). By Day 6, some non-differentiated cells in DMEM began to detach due to over confluence.…”
Section: Impedance-based Monitoring Of Stem Cell Differentiation On Cytodex Microcarriersmentioning
confidence: 90%
“…When ADSCs reached 60%-80% confluency on Cyto-MCs, differentiation process was initiated as previously described. [49][50][51] As shown in the nucleus-stained (DAPI) images of Cyto-MCs (Figure 6C), cell proliferated slower during differentiation as cell densities on Cyto-MCs cultured in DMEM were higher than in adipogenic medium (AM) and osteogenic medium (OM). By Day 6, some non-differentiated cells in DMEM began to detach due to over confluence.…”
Section: Impedance-based Monitoring Of Stem Cell Differentiation On Cytodex Microcarriersmentioning
confidence: 90%
“…In this context, a potential association of material stiffness with trophic activities has generally not yet received much attention. However, recent evidence suggests that material stiffness modulates the paracrine signaling of a few cell types [ 205 , 206 , 207 , 208 ] and even the intracellular reactive oxygen species (ROS) level in human adipose-derived MSCs (ADMSCs) [ 209 ]. One study varied either poly(ethylene)glycol diacrylate (PEGDA) hydrogel stiffness but kept the cell adhesive sites constant or varied the concentration of the cell adhesive sites.…”
Section: Immuno-modulative and Angiogenic Role Of Materials Stiffnmentioning
confidence: 99%
“…Human adipose-derived mesenchymal stem cells on mechanically tunable fibronectin-conjugated polyacrylamide (FN-PAAm) hydrogel substrates have been studied and it has been found that the intranuclear Nrf2 level of the cells grown on the soft 0.15 kPa FN-PAAm hydrogel was about three times higher compared with intranuclear Nrf2 level in the cells cultured on the hard glass surfaces. Upregulation of downstream target of Nrf2 heme oxygenase-1 was also reported [96]. So, the decrease in substrate stiffness activated Nrf2.…”
Section: Nf-κb Activationmentioning
confidence: 72%